PERSPEKTIF KELUARGA TERHADAP IBU MENYUSUSI DALAM PRAKTIK PEMBERIAN ASI EKSLUSIF DI INDONESIA: SCOPING REVIEW - Nelly Nur Laili; Machfudloh Machfudloh; Meilia Rahmawati (JURNAL MEDIA KESEHATAN, 2022)
ABSTRACT Background: The policy on exclusive breastfeeding is stipulated by the Government of Indonesia in the Law of the Republic of Indonesia number 36 of 2009 concerning Health, article 128 paragraph 1. One of the main problems to date that has caused the low success of breastfeeding in Indonesia is the factor of family support related to breastfeeding. with socio-cultural. The behavior of exclusive breastfeeding is inseparable from the family's view of the culture that has been passed down from generation to generation in the culture concerned. Thus due to the lack of support from the family due to the perspective of the family that still underestimates exclusive breastfeeding, causing the failure of exclusive breastfeeding to still be high. Methods: Literature review by searching using electronic media and the internet through a database using keywords. Result: Family support is influenced by the perspective or view and knowledge of the family on exclusive breastfeeding. Conclusion: This study concludes that the family's view of exclusive breastfeeding for infants is very important. Because a good family view will give birth to good support for mothers in breastfeeding their babies exclusively. Therefore, health workers are expected to be able to involve families in providing IEC regarding exclusive breastfeeding so that families also have a good view of exclusive breastfeeding, and mothers will get good family support in practice of exclusive breastfeeding. Keywords: Exclusive Breastfeeding, Family support, Perspective